Trade Integration and the Fragility of Trade Relationships: A Product Level Perspective - Volker Nitsch; Tibor Besedes (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We investigate the effect of economic integration agreements on the stability of international trade at the 4 digit SITC level. Using annual trade data for over 180 countries from 1962 to 2005 we examine how economic integration agreements affect the length of trade relationships, the volume at the start of new trade relationships, and how quickly trade grows within a relationship. We find evidence of an interesting dichotomy which highlights the relevance of transaction costs for exports. While economic integration increases the length of trade relationships which started prior to the agreement, it reduces the length of those started after the agreement. Similarly, economic integration increases the growth rate of relationships which started prior to the agreement, but decreases the growth rate of those that started after the agreement. With respect to starting size of trade relationships, economic integration lowers initial transaction volumes.
Keywords: F15; F14; F13; 330